INTEGRATING SURAH LUQMĀN VERSE 13 AND ANDREW NEWBERG’S NEUROSCIENCE IN CHILDREN’S SPIRITUAL-MORAL EDUCATION - Zahrotul Firdaus, Mas; Yardho, Moh.; Mukhib, Mokhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Departing from the need to understand how the moral and spirituality of children is formed based on the Qur'an and the biological condition of the brain. Purpose: This study examines the integration of the value of children's moral-spiritual education in Surah Luqmān verse 13 with Andrew Newberg's neurospiritual theory. Method: Using a qualitative method with a scientific interpretation approach and intertextual-synthesis analysis, this study examines the text of the Qur'an through the literature of interpretation and Newberg's neuroscience literature. Result: The results of the study showed a correlation between the principles of compassion-based monotheism education in Luqmān:13 and the mechanism of children's spiritual brain development, including the limbic system, spindle cells, and reflective tissues. Conclusion: This synthesis produces a model of religious education based on neurospiritual integration that can be applied in the Islamic education curriculum to foster empathy, moral awareness, and spiritual closeness of children. Implication: The practical implications of this research include the development of learning modules that pay attention to the stages of children's neurological development as well as training educators in applying integrative approaches to revelation and science.